Answer
(x + 2)² + 6 = 0
Step-by-step explanation
We are asked to express the quadratic equation in its completed square form.
The way to do this is to add and subtract the square of the half of the coefficient of x from the left hand side.
Coefficient of x = 4
Half of the coefficient of x = (4/2) = 2
Square of the half of the coefficient of x = 2² = 4
x² + 4x + 10 = 0
x² + 4x + 4 - 4 + 10 = 0
x² + 4x + 4 + 6 = 0
x² + 2x + 2x + 4 + 6 = 0
x(x + 2) + 2 (x + 2) + 6 = 0
(x + 2) (x + 2) + 6 = 0
(x + 2)² + 6 = 0
Hope this Helps!!!